Significance of SUV Max for Predicting Occult Lymph Node Metastasis and Prognosis in Early-Stage Tongue Squamous Cell Carcinoma. (30th March 2020) - Xu, Chunmiao; Li, Hailiang; Seng, Dongjie; Liu, Fei
Abstract : Objective . Our goal was to clarify the significance of SUV max for predicting occult lymph node metastasis and prognosis in early-stage tongue squamous cell carcinoma (SCC). Methods . cT1-2N0 tongue SCC patients who underwent a preoperative PET-CT examination were prospectively enrolled. The association between SUV max and occult lymph node metastasis was analyzed. The main study endpoint was locoregional control (LRC). The Cox model was used to determine the independent factors. Results . A total of 120 patients were included for analysis, and the median SUV max was 9.7. In 60 patients with an SUV max ≤9.7, 5 patients had occult metastasis; in 60 patients with an SUV max >9.7, 13 patients had occult metastasis, and the difference was significant (p = 0.041 ). In patients with an SUV max ≤9.7, the 5-year LRC rate was 93%; in patients with an SUV max >9.7, the 5-year LRC rate was 81%, and the difference was significant (p = 0.045 ). Conclusion . An SUV max >9.7 was a marker for occult lymph node metastasis and could decrease LRC in patients with cT1-2N0 tongue SCC.